Mandibular Reconstruction with Free Fibula Flap for Medication-related Osteonecrosis of the Jaw in Patients with Multiple Myeloma. Issue 10 (October 2020) - Kaoutzanis, Christodoulos; Yu, Jason W.; Lee, Z-Hye; Davary, Ashkan; Fleisher, Kenneth E.; Levine, Jamie P.
Abstract : Summary: While bisphosphonates are the cornerstone for management of multiple myeloma, they are associated with medication-related osteonecrosis of the jaw (MRONJ). There are many controversies in the management of MRONJ in this patient population. In this article, we describe a representative case and, along with a literature review, we report the outcomes of our 3 cases with multiple myeloma who underwent mandible reconstruction with vascularized fibula bone grafts after segmental mandible resection for Stage 3 MRONJ over a 3-year period. All patients were male with a mean age of 59 years. All patients had undergone therapy with bisphosphonates and had no other identifiable cause of mandible osteonecrosis. All patients had pathologic mandible fractures associated with intraoral fistulae and exposed bone. Nonsurgical management was attempted in all patients. One patient also underwent debridement of the mandible without resolution of the disease. Mandible reconstruction with an osteocutaneous free fibula flap after segmental mandible resection was performed in all 3 cases without major complications or donor site morbidity. Different bacteria were isolated from the intraoperative tissue cultures in all cases. Computed tomographic imaging revealed bony union without hardware complications in all cases. Mean follow-up was 28 months. In conclusion, we demonstrated that patients with multiple myeloma and advanced MRONJ lesions of the mandible can be managed successfully and safely by segmental resection and reconstruction with vascularized fibula bone graft.